The Key Clinical Questions of Neoadjuvant Chemoradiotherapy for Resectable Esophageal Cancer—A Review - Han, Dan; Li, Baosheng; Zhao, Qian; Sun, Hongfu; Dong, Jinling; Hao, Shaoyu; Huang, Wei (Frontiers in Oncology, 2022)
More than half of esophageal cancer (EC) patients are diagnosed at locally advanced stage, and outcomes of patients receiving surgical resection alone are still unsatisfactory, with a 5-years survival rate of 20–36%. Based on the evidence that CROSS and NEOCRTEC5010 trial provided, neoadjuvant chemoradiotherapy (nCRT) has been established as the standard therapy for patients with locally advanced EC. But there are still many concerned clinical questions that remain controversial such as radiation dose, appropriate patients selection, the design of the radiation field, the time interval between chemoradiotherapy and surgery, esophageal retention and so on. With immune checkpoint inhibitors (ICIs) having rapidly been becoming a mainstay of cancer treatment, along with radiation, chemotherapy and surgery, the combination mode of immunotherapy also become a hot topic of discussion. Here, we try to provide constructive suggestions to answer the perplexing problems of clinical concerned for the well progress of nCRT for EC in the future.